Propofol Requirement and EEG Alpha Band Power During General Anesthesia Provide Complementary Views on Preoperative Cognitive Decline - Touchard, Cyril; Cartailler, Jérôme; Levé, Charlotte; Serrano, José; Sabbagh, David; Manquat, Elsa; Joachim, Jona; Mateo, Joaquim; Gayat, Etienne; Engemann, Denis; Vallée, Fabrice (Frontiers in Aging Neuroscience, 2020)
Background: Although cognitive decline (CD) is associated with increased post-operative morbidity and mortality, routinely screening patients remains difficult. The main objective of this prospective study is to use the EEG response to a Propofol-based gen-eral anesthesia (GA) to reveal CD. Methods: 42 patients with collected EEG and Propofol target concentration infusion (TCI) during GA had a preoperative cognitive assessment using MoCA. We evaluated the per-formance of three variables to detect CD (MoCA < 25 points): age, Propofol requirement to induce unconsciousness (TCI at SEF95: 8-13 Hz) and the frontal alpha band power (AP at SEF95: 8-13 Hz). Results: The 17 patients (40%) with CD were significantly older (p < 0.001), had lower TCI (p < 0.001) and AP (p < 0.001). We found using logistic models that TCI and AP were the best set of variables associated with CD (AUC: 0.89) and performed better than age (p < 0.05). Propofol TCI had a greater impact on CD probability compared to AP, alt-hough both were complementary in detecting CD. Conclusion: TCI and AP contribute additively to reveal patient with preoperative cogni-tive decline. Further research on post-operative cognitive trajectory are necessary to con-firm the interest of intra operative variables in complement to cognitive evaluation or when it could not to be done.